The distribution and persistence of primate species in disturbed and converted forest landscapes in Sabah, Malaysia: preliminary results - Henry Bernard; Rayner Bili; Oliver R Wearn; Goro Hanya; Abdul Hamid Ahmad (2014)
As disturbance and conversion of tropical rainforests due to man-made activities in many parts of the world continue at alarming rates, the future of many tropical rainforest species will depend more than ever on the effective management of a mixture of human-modified landscape. We studied the non-human primate community by direct and indirect sightings across a gradient of habitat disturbance - from old growth forest to heavily logged forest to oil palm plantation- in and around the Stability of Altered Forest Ecosystems (SAFE) Project experimental area in Kalabakan Forest Reserve, south central part of Sabah, Malaysian Borneo. Here we provide the preliminary analysis of our data. We confirmed the existence of nine, of the total of 10 species of non-human primates found in Sabah, within the surveyed areas. By using occupancy analysis we found no evidence of differential habitat disturbance effects on the primate community. We also found no evidence supporting differential habitat disturbance effects on the primate community based on animal body size or feeding habit. The lack in such evidences is surprising and it is likely due to the artifact of the small data set of this study. Interestingly, however, the presence of eight species of primates within the heavily logged forest sampling sites, which included Bornean endemic species and species of high conservation concern, e.g. orangutan, proboscis monkey and Bornean gibbon, shows that even highly disturbed forests in Sabah are still valuable for primate conservation.